Prevalence of methicillin resistant Staphylococcus aureus in a tertiary hospital of Nepal - Rajbhandari, Piyush; Maharjan, Shanta; Pradhan, Prasil; Aryal, Sushant (Journal of Patan Academy of Health Sciences, 2024)
Introduction: Methicillin resistant Staphylococcus aureus (MRSA) is one of the leading causes of healthcare associated infection. It causes different types of difficult-to-treat infections as these pathogens are resistant to β-lactam antibiotics. The changing epidemiology, ever-increasing prevalence and changing trends of susceptible antibiotics is a global concern. The aim of this study was to evaluate the prevalence of MRSA isolated from various samples. Method: It was a hospital based descriptive cross-sectional study conducted at Patan Hospital, Patan Academy of Health Sciences. All the records of the patient whose culture and sensitivity report yielded Staphylococcus aureus from 1st January 2021 to 31st December of 2023 was extracted from the hospital electronic database and analyzed. Ethical approval was taken from the Institutional Review Committee. Result: Out of 1259 Staphylococcus aureus isolates, 570(45.14%) were MRSA out of which, 380(66.67%) were identified from samples collected through outpatient department visits. MRSA had higher sensitivity to vancomycin (100%), linezolid (97.57%), doxycycline (93.17%) and chloramphenicol (84.67%). The sensitivity was concerning to clindamycin (39.57%), trimethoprim-sulfamethoxazole (36.23%), azithromycin (32.73%) and erythromycin (27.87%) and very alarming to gentamicin (19.00%), ofloxacin (5.57%) and ciprofloxacin (4.40%). Conclusion: The prevalence of MRSA infection is alarming in the patients visiting our outpatient departments and has shown no signs of improvement over the past three years. Gradual decline to once sensitive drugs is now being observed. To address this issue, continuous surveillance, good Infection control practices and judicious antibiotic use are needed not only in hospitals but also in community settings.